Design of Wide-Band Bandpass Filter Using Composite Right/Left-Handed Transmission Line Structure. (11th April 2016) - Ren, Baoping; Liu, Haiwen; Guan, Xuehui; Wen, Pin; Xiao, Xiang; Ma, Zhewang
Abstract : A wide-band microstrip bandpass filter (BPF) based on the improved composite right/left-handed transmission line (CRLH-TL) structure is presented in this paper. Compared to the traditional CRLH-TL with via hole, the improved one is an all-planar structure, which owns the advantage of fabrication and loss. The equivalent lossless LC circuit model of the proposed structure is established. EM software Sonnet is adopted to design the wide-band filter with bandwidth of 1.4 GHz (from 1.9 GHz to 3.3 GHz). The circuit occupies only 20.6 × 12.8 mm 2 . Finally, the fabrication and measurement are implemented. A good agreement between simulation and measured results verifies the validity of the design methodology.